Vaccinating children against diphtheria, pertussis, tetanus and poliomyelitis in Nepal - Jha, N; Niraula, SR (Health Renaissance, 2011)
DOI: http://dx.doi.org/10.3126/hren.v9i2.4984 Health Renaissance 2011: Vol.9 (No.2): 112-115